Performance Analysis of the Effect of Nonlinear Low Noise Amplifier for Wideband Spectrum Sensing in the Poisson Field of Interferers - Bipun Man Pati; Attaphongse Taparugssanagorn (Journal of Computer Networks and Communications)
A cognitive radio (CR) device likely consists of a low-cost low noise amplifier (LNA) due to the mass-production reason. Nevertheless, the operation of a low-cost LNA becomes highly nonlinear causing intermodulation (IM) interference. The most important task of CR devices is to sense the wideband spectrum to increase opportunistic throughput. In noncooperative secondary networks, the IM interference usually can be ignored for the narrowband spectrum sensing, while the IM interference needs to be taken into account along with interference from other CR devices in the wideband case. Our contribution is to study the effects of a nonlinear LNA for the second case in environments modeled by Poisson field of interferers reflecting more realistic scenario. As shown in the simulation results, the performance of the receiver is degraded in all the cases due to the nonlinearity of LNA. The adaptive threshold setting based on the multivariate Gaussian mixture model is proposed to improve the receiver performance.